EFL TEACHERS’ CHALLENGES IN TEACHING SPEAKING AT SMAN 3 BANJARMASIN - Rochmah, Ziana Nor; Kamal, Sirajuddin; Hidayat, Fahmi (STKIP Pesisir Selatan, 2025)
In Indonesia, English is taught as a foreign language. EFL students typically study English only in formal educational settings such as classroom and have limited opportunities to practice speaking the language in real-life situation. Hence, English teacher particularly in EFL countries, teaching speaking skills can be challenging. The objective of this is to identify specific teaching challenges and the efforts taken by teachers to address them. A qualitative descriptive method was used, involving interviews, observations, and documentation with two English teachers. The findings reveal seven key challenges: noise level, students speaking L1 language inappropriate time, limited time, unengaged students, the role of exposure in English, handling lower English classes and large class. To address these issues, teachers implemented five main strategies: keep student in the target language, using group work, making a careful choice of topic, teachers are placed to provide comprehensible input and activity on easy language. Many studies have focused only on the challenges in teaching speaking. However, they do not explain the efforts teacher used to overcome them. Analyzing the challenges and efforts in teaching speaking can provide understanding of how teacher overcome these challenges in classroom.